2022
DOI: 10.1093/ajh/hpac088
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-Day Readmission Rate Among Patients With Hypertensive Crisis: A Nationwide Analysis

Abstract: Background Hypertensive crisis is a life-threatening condition, further classified as hypertensive emergency and hypertensive urgency based on the presence or absence of acute or progressive end-organ damage, respectively. Readmissions in hypertensive emergency have been studied before. We aimed to analyze 30-day readmissions using recent data and more specific ICD-10-CM coding in patients with hypertensive crisis. Methods In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…A larger study of ≈75 000 patients hospitalized with hypertensive urgency found that 10% were readmitted within 30 days, but reasons for readmissions were not reported. 8 In this context, our study reveals the novel finding that patients discharged home from the ED with a diagnosis of hypertensive urgency faced a significantly elevated short-term relative risk of MACE, although absolute event rates were low. Current emergency medicine guidelines offer no strategies to identify patients with hypertensive urgency who are at heightened short-term MACE risk 14 ; our results, therefore, suggest a need for prospective studies to improve disease detection and risk stratification among ED patients diagnosed with hypertensive urgency.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…A larger study of ≈75 000 patients hospitalized with hypertensive urgency found that 10% were readmitted within 30 days, but reasons for readmissions were not reported. 8 In this context, our study reveals the novel finding that patients discharged home from the ED with a diagnosis of hypertensive urgency faced a significantly elevated short-term relative risk of MACE, although absolute event rates were low. Current emergency medicine guidelines offer no strategies to identify patients with hypertensive urgency who are at heightened short-term MACE risk 14 ; our results, therefore, suggest a need for prospective studies to improve disease detection and risk stratification among ED patients diagnosed with hypertensive urgency.…”
Section: Discussionmentioning
confidence: 71%
“…2 Prior studies have demonstrated a heightened short-term risk of major adverse cardiovascular events (MACEs) after hospitalizations for hypertensive emergencies. 7,8 However, it remains uncertain whether hypertensive urgency, defined as severe blood pressure elevation without acute or impending target-organ damage or dysfunction, 2 is associated with an increased risk of subsequent MACE. [9][10][11][12][13] The American College of Emergency Physicians has noted in a clinical policy statement that little evidence exists to guide practitioners as to how they should evaluate, treat, and arrange follow-up for the large number of patients with hypertensive urgency in the ED.…”
mentioning
confidence: 99%
“…The fact that there were a similar number of HU and HE patients among the deceased, despite the HE group being much larger, further confirms this. Other studies also found higher mortality rates in HE patients [10,12,13].…”
Section: Discussionmentioning
confidence: 80%
“…Hypertension urgencies is a group of clinical syndromes caused by an acute increase in blood pressure with or without damage to target organs. [27][28][29] Hypertension urgencies consists of two categories: hypertensive emergency and hypertensive subemergency. 29 Hypertensive emergency refers to a severe increase in blood pressure within a short period of time [usually systolic blood pressure (SBP)> 180 mmHg and/or diastolic blood pressure (DBP)> 110 mmHg accompanied by progressive target organ damage.…”
Section: Discussionmentioning
confidence: 99%
“…However, oral administration of antihypertensive drugs should be performed immediately to evaluate and monitor possible target organ 3984 damage, such as to the heart, brain, and kidney, and also to determine the possible cause of blood pressure increase. [27][28][29][30] A number of previous studies have found that sleep is associated with the occurrence and fluctuation of hypertension. Meng and He showed that a shorter sleep duration and difficulty in falling asleep may increase blood pressure.…”
Section: Discussionmentioning
confidence: 99%